Evolution of pits at the surface of 67P/Churyumov-Gerasimenko - Benseguane,S; Guilbert-Lepoutre,A; Lasue,J; Besse,S; Leyrat,C; Beth,A; Sitja,MC; Grieger,B; Capria,MT (Astronomy and Astrophysics: a European journal, 2022)
Context. The observation of pits at the surface of comets offers the opportunity to take a glimpse into the properties and the mechanisms that shape a nucleus through cometary activity. If the origin of these pits is still a matter of debate, multiple studies have recently suggested that known phase transitions (such as volatile sublimation or amorphous water ice crystallization) alone could not have carved these morphological features on the surface of 67P/Churyumov-Gerasimenko (hereafter 67P).Aims. We want to understand how the progressive modification of 67P’s surface due to cometary activity might have affected the characteristics of pits and alcoves. In particular, we aim to understand whether signatures of the formation mechanism of these surface morphological features can still be identified.Methods. To quantify the amount of erosion sustained at the surface of 67P since it arrived on its currently observed orbit, we selected 380 facets of a medium-resolution shape model of the nucleus, sampling 30 pits and alcoves across the surface. We computed the surface energy balance with a high temporal resolution, including shadowing and self-heating contributions. We then applied a thermal evolution model to assess the amount of erosion sustained after ten orbital revolutions under current illumination conditions.Results. We find that the maximum erosion sustained after ten orbital revolutions is on the order of 80 m, for facets located in the southern hemisphere. We thus confirm that progressive erosion cannot form pits and alcoves, as local erosion is much lower than their observed depth and diameter. We find that plateaus tend to erode more than bottoms, especially for the deepest depressions, and that some differential erosion can affect their morphology. As a general rule, our results suggest that sharp morphological features tend to be erased by progressive erosion.Conclusions. This study supports the assumption that deep circular pits, such as Seth_01, a